Inhabiting drawings: an art teching experience about everyday space. (Revista Apotheke, 2021)
The article deals with an art teaching activity with productions of drawings aimed at domestic environments in times of pandemic. Based on a methodological approach of critical inquiry and the experience of making art, this activity is based on Deweyan themes about aesthetic experience. (DEWEY, 2010) and in the education of visual culture (AGUIRRE, 2011; HERNÁNDEZ, 2011; MARTINS, 2007; 2009) about image and everyday life (ALVES, 2015). The production of authorial drawings by students in the 2nd year of Integrated Technical High School at the Federal Institute of Amapá - IFAP also discusses ways of representing spaces and experiences in the context of social isolation. Eight are the works selected to compose this article, as the analysis of the drawings produced is of an interpretative character on images with reference to qualitative research (ANDRÉ, 2005; GASKELL, BAUER, 2002). The visual compositions are grouped as a result of two analysis criteria descriptive spaces and projected spaces, in which the drawings as a whole move between the description of everyday spaces and constitute processes of subjectivation of spaces as metaphorical ways of perceiving, making and designing art, artifacts and spaces related to the habitat.